THE APPLICATION OF DIFFERENT CRIMINAL SANCTIONS AGAINST DRUG ABUSERS IS CONNECTED WITH ARTICLE 112 PARAGRAPH (1) OF LAW NUMBER 35 OF 2009 CONCERNING NARCOTICS - Habibah, Tira; Hidayat, Anwar; Dewi, Sartika (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2024)
The application of different criminal sanctions or criminal disparities is the application of criminal sanctions, in this case the application of criminal sanctions that are not the same or for criminal acts whose dangerous nature can be compared without a clear basis for awarding them. The problem raised in this study is how the Judge considers in applying different criminal sanctions against narcotics abusers in decision number 203/Pid.Sus/2021/Pn.Blt and number 295/Pid.Sus/ 2021/PN.Blt and what are the factors that result in differences in the application of criminal sanctions to the two decisions above. This study uses a normative juridical approach. The results of this study are the Judge's considerations in decision number 203/Pid.Sus/2021/Pn.Blt The Judge based on the legal facts revealed at the trial that the Defendant Yamsul Arifin was an abuser for himself so that the Judge in applying criminal sanctions deviated from special minimum criminal provisions in Article 112 paragraph (1), while the Judge's consideration in decision number 295/Pid.Sus/2021/Pn.Blt that the Defendant Elysa Sadola is a trafficker so the Judge continues to apply a sentence between the minimum and maximum limits specifically in Article 112 paragraph (1) Law Number 35 of 2009 concerning Narcotics. Then the factors that result in the application of different criminal sanctions against narcotics abusers in the two decisions are differences in legal facts revealed in court, there are multiple interpretations in Article 112 paragraph (1), discretion or freedom of judges, and the absence of sentencing guidelines.